Factors affecting poverty in rural Bangladesh: An analysis using multilevel modelling (Journal of the Bangladesh Agricultural University, 2018)
Poverty is a multi-faced problem in the developing world and it is much more complex in rural settings. Hence, policy formulation based on national level studies sometimes fails to find remedies of rural poverty. Thus, the present study aims to identify the determinants of poverty in rural Bangladesh using the nationally representative Household Income and Expenditure Survey (HIES) 2010 data. The HIES follows a hierarchical structure hence, two-level random intercept binary logistic regression models were used to capture the unobserved heterogeneity between communities along with revealing important factors associated with poverty. The analyses found that 32% of the households were absolute poor and 19% were extremely poor in rural Bangladesh. The potential factors having significant association with poverty were found to be age and education of household head, division, household size, household types, number of dependents, per capita income, household own land, access to electricity, amount of cultivable land, engagement in livestock and farm forestry, household non-agricultural assets, number of male earner and number of female earner in the family. Significant community-level variations were observed in the analyses which emphasis the need for special attention on the poor performing communities. Specific policy recommendations have been suggested for the poverty alleviation of rural households in Bangladesh.J. Bangladesh Agril. Univ. 16(1): 123-130, April 2018